2021
DOI: 10.1039/d1na00013f
|View full text |Cite
|
Sign up to set email alerts
|

Polarisation tuneable piezo-catalytic activity of Nb-doped PZT with low Curie temperature for efficient CO2 reduction and H2 generation

Abstract: The reduction of CO2 into useful hydrocarbon chemicals has attracted significant attention in light of the depletion in fossil resources and the global demand for sustainable sources of energy. In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 78 publications
0
31
0
Order By: Relevance
“…Piezocatalytic Driven CO 2 Reduction: Piezocatalytic CO 2 reduction can be a by-product of piezocatalytic water splitting. Zhang et al [208] reported an efficient CO 2 reduction based on Nb doped Pb 0.99 Zr 0.95 Ti 0.05 Nb 0.02 O 3 (PZTN) (Figure 52a). The Nb doping can tune the T C to close to room temperature, [209] which gives rise to high piezoelectricity in order to trigger the reduction of CO 2 .…”
Section: Co 2 Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Piezocatalytic Driven CO 2 Reduction: Piezocatalytic CO 2 reduction can be a by-product of piezocatalytic water splitting. Zhang et al [208] reported an efficient CO 2 reduction based on Nb doped Pb 0.99 Zr 0.95 Ti 0.05 Nb 0.02 O 3 (PZTN) (Figure 52a). The Nb doping can tune the T C to close to room temperature, [209] which gives rise to high piezoelectricity in order to trigger the reduction of CO 2 .…”
Section: Co 2 Reductionmentioning
confidence: 99%
“…c) Enhanced CO production and H 2 generation via piezo-catalytic and sonochemical effects. Reproduced with permission [208]. Copyright 2021, Royal Chemical Society.…”
mentioning
confidence: 99%
“…electric potential, which provides an alternative approach to determine the piezopotential amplitude of particles. [39] Here, V represents the piezopotential, d ij is the piezoelectric coefficient, e r is relative permittivity, e 0 is the electrical permittivity of the free space, s is the loading stress,and w is the width of the piezoelectric particle.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a theoretical equation [Eq. 3] was introduced to calculate particle piezoelectric potential, which provides an alternative approach to determine the piezopotential amplitude of particles [39] trueV=(dij/ϵrϵ0)σw …”
Section: Screening Charge Effectmentioning
confidence: 99%
“…Piezoelectric owns high piezoelectric coefficient in the vicinity of the Curie temperature. To take full use of this feature and mechanical energy, Zhang et al [342] exploited a solid state reaction to prepare Nb-doped lead zirconate titanate with low Curie temperature (≈38 °C) approaching to room temperature for piezocatalytic CO 2 reduction. The large variation of polarization intensity at the temperature near T c , which was derived from periodic ultrasonic acoustic pressure, induced more piezoelectric free charges to interact with CO 2 molecules so as to acquire optimal piezocatalytic activity with a CO evolution rate of 789 µmol g −1 h −1 when the catalyst dosage was 0.1 g L −1 .…”
Section: Piezocatalytic Energy Carrier Production By Titanatesmentioning
confidence: 99%